Dynamic responses of mini-TLP (seastar) - Abang Mohamad Zayd bin Abang Othman, Abang Mohamad Zayd (2010)
The focus of this research is on the Mini-Tension Leg Platform (mini-TLP). It is one of the available offshore floating structures that are available in the industry. To make sure that the construction of a mini-TLP is profitable, the optimum design need to be designed and there is a need to study more on the performance of this particular structure. Similar to other offshore structures, mini-TLP is also exposed to the intense action of wind, current and wave in the sea.